The impact of ability grouping on college student's performance in introductory geology labs at a Midwestern university - Bosco, Kimberly Renee (Kansas State University, 2009)
There have been numerous studies done during the past hundred years on ability grouping. The majority of research has focused on the elementary and secondary levels, with very little done at the post-secondary level of education. Research shows at the K-12 levels high achieving students have a greater level of learning when placed in groups together. Mid- level students also show higher achievement in homogeneous groupings. Both high and mid-level students benefit from heterogeneous grouping, but with smaller gains. Lower ability students placed in homogenous groups have shown significant gains, but still perform better when grouped heterogeneously compared with classes that are not grouped by ability. All students show increases in learning when placed in small groups of any kind. Mid-level and low achieving students have higher levels of learning when they are taught by someone determined to close the gap, who takes the students' abilities into consideration, and focuses on increasing those abilities. Unfortunately, this often does not happen, and when students are grouped by ability, the higher achieving students do well, and the rest fall further behind. This graduate research looks at the impact of skill grouping at the university level. Rather than separating students into different classes by ability, students were placed in purposeful groups within the class. Overall both homogeneous and heterogeneous groupings performed better than the control self-selected sections. One homogeneous quartile showed significant improvement in performance compared to the heterogeneously grouped students, but another homogeneous quartile showed a significant decline in scores. Gains in one subset of student should not come as a detriment to another subset of students, so homogeneous grouping is not recommended. Of the three grouping methods, only heterogeneous grouping showed significant increases in scores without harm to other students, and for this reason, this study recommends using a heterogeneous method of grouping students in future GEOL 103 classes.
Keywords: Ability grouping; Science; Higher education; Education, Higher (0745); Education, Sciences (0714); Geology (0372)